2019
DOI: 10.33331/rechtsvinding.v8i2.319
|View full text |Cite
|
Sign up to set email alerts
|

Koherensi Pengaturan Illegal, Unreported, and Unregulated Fishing Di Indonesia

Abstract: <div class="page" title="Page 1"><div class="section"><div class="layoutArea"><div class="column"><p><span>Sumber daya hayati perikanan adalah sumber daya yang perlu dilindungi dan dioptimalkan pengolahannya, namun kejahatan di bidang perikanan semakin meningkat. Hukum internasional kemudian mengklasifikasikan kejahatan perikanan ke dalam</span><span>Illegal, Unreported, and Unregulated Fishing</span><span>. Pertanyaan dalam penelitian ini adalah baga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…These goals correspond to the achievement of both the Aichi Targets (Convention on Biological Diversity Strategic Plan 2011-2020) and Sustainable Development Goal 14 "Life Under Water" [37]. As an archipelagic state possessing 6.4 million km 2 of water areas [38], Indonesian seas are easy targets for illegal, unreported, and unregulated fishing (IUU Fishing, IUUF) practices [39]. IUU Fishing does not only impact the economic sector, but also the sustainability of marine and coastal environment.…”
Section: Indonesia's Goals and Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These goals correspond to the achievement of both the Aichi Targets (Convention on Biological Diversity Strategic Plan 2011-2020) and Sustainable Development Goal 14 "Life Under Water" [37]. As an archipelagic state possessing 6.4 million km 2 of water areas [38], Indonesian seas are easy targets for illegal, unreported, and unregulated fishing (IUU Fishing, IUUF) practices [39]. IUU Fishing does not only impact the economic sector, but also the sustainability of marine and coastal environment.…”
Section: Indonesia's Goals and Commitmentmentioning
confidence: 99%
“…Studies also revealed deficiencies in the regulation of IUU Fishing under the Fisheries Law, leading to the urgency of reformulation that can optimize the protection of biological -including fisheryresources, this includes regulations on corporate criminal liability for IUUF practices. In addition, in terms of implementation, coordination between the central and local governments is highly required in establishing an appropriate mechanism to prevent and eradicate the practice of IUU Fishing [39,42].…”
Section: Indonesia's Goals and Commitmentmentioning
confidence: 99%
“…These factors give rise to an interest in Vietnam in collaborating to combat illegal fishing with Indonesia, namely; (1) the interest in protecting Vietnam's marine environment (Akbar, 2019). One of the points in this collaboration discusses cooperation in improving the management of capture fisheries in each country so that this collaboration can help…”
Section: Declaration Of Indonesia -Vietnam As a Medium-term Goalmentioning
confidence: 99%
“…Article 84 paragraph 1 the perpetrator is more common, namely "everyone". While paragraphs 2, 3, and 4 provide different subject specifications, namely the skipper or leader of the fishing boat, fishing expert, and crew members (paragraph 2), then paragraph (3) provides subject specifications for fishing boat owners, fishing company owners, the person in charge fishing companies, and/or fishing boat operators, and paragraph (4) defines the owner of the fish farming company, the power of attorney for the owner of the fish farming company, and/or the person in charge of the fish farming company (Akbar, 2019).…”
Section: Corporations As Perpetrators Of Fisheries Crimesmentioning
confidence: 99%